Metode Bermain Suku Kata Terhadap Keterampilan Membaca Permulaan Pada Siswa SD - Ferdian Kaswari; Muhammad Erfan; Muhammad Tahir (Journal of Classroom Action Research, 2023)
The Influence of Syllable Playing Method Against Beginning Reading Skills in Class II Students of SD Negeri 4 Cakranegara Academic Year 2022/2023. Thesis, Department of Education, Teaching Faculty and Educational Sciences, University of Mataram. Advisor: Muhammad Erfan,M.Pd. and Muhammad Tahir, M.Sn.This study aims to determine whether there is influence of use the method of playing syllables on students' beginning reading skills II SD Negeri 4 Cakranegara. This research is a quantitative research with the research design used is One-Group pretest-posttest. Data collection techniques used are tests and observations. Data on This study was analyzed using the t-test. After applying the syllable playing method, the average increase was obtained initial reading skills from 65.72 to 78.64 for cognitive aspects, as well as psychomotor aspects from previously 58.92 to 73.60. From the results of the Mann-Whitney U test, the value of Sig. 2-tailed by 0.015 smaller than 0.05 so it can be concluded that there is an influence the use of the method of playing syllables on reading skills beginning of class II students of SD Negeri 4 Cakranegara.